Construction and validation of an instrument to assess the university dropout intention formation process UDIFP-29 - Yaranay López Angulo; Karla Muñoz-Inostroza; Fabiola Sáez-Delgado; Javier Mella-Norambuena; Carlos Patricio Zalaquett (PLoS ONE, 2026)
A significant body of research supports the importance of addressing university students’ dropout intention, the process through which university students form the intention to dropout from their studies. However, available measurement tools failed to account for how dropout intention is formed over time. This research aimed to fill that gap by developing and validating a multidimensional self-report instrument to assess how the intention to dropout from the university is formed. Three studies were designed for this purpose. Study 1 used focus groups to explore how the intention to dropout emerges in freshman students enrolled at a university, with the purpose of developing a theoretical model to explain how the intention to dropout emerges. Study 2 focused on the content validation of the preliminary version of the instrument, which was carried out by expert judgment. Study 3 examined the construct validity of the instrument using exploratory and confirmatory factor analysis and analyzing its convergent and divergent validity. The results showed a model with good adjustment and adequate internal consistency indexes. In general, the instrument has adequate psychometric properties, proving to be reliable and valid for measuring the process of forming early university dropout intention. Use of this instrument will allow the design of timely strategies and interventions to reduce dissatisfaction, dropout ideation and dropout.